2021
DOI: 10.1007/s13340-021-00490-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of glycemic control and anthropometric measurement among type 2 diabetes mellitus: a cross-sectional study

Abstract: Introduction Maintaining good glycemic control is the main therapeutic target for diabetes mellitus (DM) patients. Nevertheless, due to complex factors, the majority of patients worldwide persist poorly controlled. Hence the study was conducted to determine the association of anthropometric measurement and other factors with glycemic control among type 2 DM patients. Methods An institutional-based cross-sectional study was conducted among 366 type 2 DM patients from October-1 to November 30/2019. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…24 In this study, 39% reported poor adherence. The prevalence of poor adherence in the present study was similar to the studies reported from India, 19,25,26 Brazil, 27 Ethiopia, 28 and Tanzania. 29 In contrast to our findings, a study from Kerala, India, reported a much higher prevalence (74%), but the study was reported from a general population.…”
Section: Discussionsupporting
confidence: 90%
“…24 In this study, 39% reported poor adherence. The prevalence of poor adherence in the present study was similar to the studies reported from India, 19,25,26 Brazil, 27 Ethiopia, 28 and Tanzania. 29 In contrast to our findings, a study from Kerala, India, reported a much higher prevalence (74%), but the study was reported from a general population.…”
Section: Discussionsupporting
confidence: 90%
“…In the present meta-analysis, the pooled prevalence of good and poor glycemic control in Ethiopia was estimated using 46 articles. 19,24,25, 47 - 89 In a random effect model, the pooled prevalence of good glycemic control was found to be 38.08% (95% CI: 34.08, 42.08) with significant heterogeneity among the included articles ( I 2 = 96.57%, P < .001) ( Figure 2 ). The potential sources of higher heterogeneity were investigated further.…”
Section: Resultsmentioning
confidence: 99%
“…Of these articles, 9 articles were excluded from meta-analyses of different factors due to the fact that some articles did not report factors or did not properly report the factors. 25, 47 - 54 The pooled prevalence of good and poor glycemic control in Ethiopia was estimated using all 46 articles ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Those diagnosed with DM for more than twenty years prior had greater odds of developing suboptimal glycemic status compared to those who had been diagnosed with DM for less than twenty years. This result was confirmed by studies in Ethiopia [37], Saudi Arabia [38], northern Thailand [23], Nepal [39], and India [40], which discovered that people who were diagnosed with diabetes more than ten years ago were more likely to have poor glycemic control than those diagnosed with diabetes less than ten years. A prolonged period of T2DM is often accompanied by a gradual reduction of insulin production due to pancreatic β-cell failure, which in turn increases insulin resistance, making it more difficult to manage blood glucose [27].…”
Section: Discussionmentioning
confidence: 65%